The relationship of rewards, workload and working environment on job satisfaction among bank officer - Muhammad Haziq, Hamidun (2020)
Employee attitudes are very significant to management and organizations since they determine the behaviour of employees in an organization. It is believed that employees who were satisfied is usually to be more productive than employees who are dissatisfied towards their job. Satisfied employees are the creator of a pleasant atmosphere within organization. Therefore, job satisfaction has been imposing topic in the studies. The purpose of this study is to examine whether reward, workload and working environment has related to the employees’ perceptions give impact towards job satisfaction in banking sector in Malaysia. Based on the analysis it was found that rewards and working environment have significant relationship with job satisfaction. Hierarchically, these two factors are found to be among the strongest predictor variables to compliance with job satisfaction in banking sectors. Recommendations and implications for future research and practice were also discussed.